Effect of Sunflower (Helianthus annus L.) Hulls with Different Particle Sizes on Growth Performance and Physiological Responses of Broiler Chickens Fed Different Levels of Protein - Najibeh Beigzadeh; Smayyeh Salari; Faegheh Zaefarian; Shima Hosseinifar (پژوهشهای علوم دامی ایران)
Introduction: In broilers, dietary fiber stimulates the production of hydrochloric acid and bile acids and improves amylase activity, leading to better nutrient utilization (Hetland et al., 2002). A well-developed gizzard also enhances reverse peristalsis, which churns food back up the digestive tract. A reduced-crude protein (CP) diet are typically formulated by decreasing soybean meal and increasing feed grains (such as maize or wheat), along with higher inclusions of non-bound (crystalline and synthetic) amino acids to meet nutritional requirements. Studies (Van Harn et al., 2017) have shown that CP reductions (20-30 g/kg) in Ross 308 broiler diets can be achieved without compromising live weight gain or feed intake. Notably, these diets even show a significant improvement in feed conversion ratio (FCR) with a 3.5% decrease. Dietary fiber with increased particle size may enhance foregut development more effectively in poultry fed diets moderately low in crude protein. This study investigates the performance of broilers fed on low-density crude protein diets with increasing particle size of sunflower (Helianthus annus L.) hulls.Materials and Methods: This experiment aimed to examine the effect of sunflower hull particle size on the performance and physiological response of broiler chickens fed with different protein levels. A completely randomized design based on a 3 × 2 factorial arrangement, comprising 6 treatments (6 replicates per treatment, 10 birds per replicate). The treatments included 3 types of dietary sunflower hull types (without hulls, 4% with 1 mm particle size, and 4% with 5 mm particle size) and 2 crude protein (CP) levels (normal and a 10% reduction). Feed intake (FI) and body weight gain (BWG) were recorded, and the feed conversion ratio (FCR) was calculated. To determine ideal nutrient digestibility, chickens were fed 3 g/kg of chromium oxide from days 21 to 25. On day 25, ileum contents from 2 birds per replicate were collected and stored at -20°C. The cecal microbial population was assessed at 42 days of age. Data were analyzed using SAS software and the GLM procedure. Duncan's multiple range test was used for mean comparison at a 5% significance level.Results and Discussion: The results indicated that incorporating sunflower hulls (SFH) in the diet increased FI, except during the starter period, and improved FCR in both the starter and grower periods. The high amount of FI in the treatments containing SFH may be related to the high level of lignin and cellulose, because it increases the rate of passage of digestive juice through the digestive tract and ultimately increases FI (González-Alvarado et al., 2010). Broilers fed coarse SFH showed increased relative weights of the carcass, gastrointestinal tract, gizzard. The use of a rich source of insoluble fiber in the diet can increase the growth of the digestive system, especially provetriculus and gizzard (Jimenez-Moreno et al., 2013). The apparent digestibility of crude protein improved by coarse SFH with low crude protein. The positive effect of fiber on the digestibility of raw protein can be attributed to the increase in pepsin activity and the increase in hydrochloric acid production (Gabriel et al., 2003). Both fine and coarse SFH in the diet enhanced the Lactobacillus population. Similarly, other researchers also reported that feeding broiler chickens with dietary lignocellulose leads to an increase in the presence of Lactobacillus species (Bogusławska-Tryk et al., 2015).Conclusion: Overall, the study results indicate that adding coarse sunflower hulls to the diet can enhance broiler growth performance. This improvement is achieved by increasing the digestibility of crude protein, as well as boosting the Lactobacillus population. Additionally, using coarse sunflower hulls led to an increase in the relative weight of the carcass and thighs.